2018
DOI: 10.1111/vsu.12960
|View full text |Cite
|
Sign up to set email alerts
|

Complications associated with closed castration using the Henderson equine castration instrument in 300 standing equids

Abstract: Objective: To describe a closed castration technique in standing equids, report associated complications, and identify potential risk factors. Study design: Prospective cohort study of 300 standing equids that were castrated with the Henderson Equine Castrating Instrument. Methods: Thirteen participating veterinarians recorded intraoperative difficulties and postoperative complications. Descriptive statistics, univariate analyses with Fisher's exact tests, and logistic regressions were used to evaluate intraop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Intraoperative risk factors include breaks in sterility, difficult surgical access, intrascrotal or tunic haematomas, poor surgical technique, poorly functioning emasculators or inappropriate emasculator use (Hodgson & Pinchbeck, 2019;Mason et al, 2005;Schumacher, 2019) Instrument is a pliers-like instrument attached to a power drill, that twists the spermatic cord, rather than cutting, resulting in sealing the severed vessels. In one report using the Henderson emasculators, haemorrhage was not reported as a complication (Hinton et al, 2019) and in another only 1% (3/300) cases had postoperative haemorrhage (Racine et al, 2019) and 2 of these cases were in donkeys.…”
Section: Haemorrhagementioning
confidence: 97%
See 1 more Smart Citation
“…Intraoperative risk factors include breaks in sterility, difficult surgical access, intrascrotal or tunic haematomas, poor surgical technique, poorly functioning emasculators or inappropriate emasculator use (Hodgson & Pinchbeck, 2019;Mason et al, 2005;Schumacher, 2019) Instrument is a pliers-like instrument attached to a power drill, that twists the spermatic cord, rather than cutting, resulting in sealing the severed vessels. In one report using the Henderson emasculators, haemorrhage was not reported as a complication (Hinton et al, 2019) and in another only 1% (3/300) cases had postoperative haemorrhage (Racine et al, 2019) and 2 of these cases were in donkeys.…”
Section: Haemorrhagementioning
confidence: 97%
“…The Henderson Equine Castrating Instrument is a pliers‐like instrument attached to a power drill, that twists the spermatic cord, rather than cutting, resulting in sealing the severed vessels. In one report using the Henderson emasculators, haemorrhage was not reported as a complication (Hinton et al, 2019) and in another only 1% (3/300) cases had postoperative haemorrhage (Racine et al, 2019) and 2 of these cases were in donkeys.…”
Section: Complicationsmentioning
confidence: 99%
“…Antimicrobials are not routinely used by some surgeons for castration (David Levine, personal communication) (Crandall et al, 2020;Hinton et al, 2019) with a complication rate that is no different to the reported complication rate of 10% (Kilcoyne, 2013). In two other studies, prolonging antimicrobial prophylaxis had no effect on swelling or infection (Racine et al, 2019) and horses receiving prolonged SAP (days) had a complication rate of 60% (Rosanowski et al, 2018). While there is no strong evidence either way, SAP for castration is likely unnecessary.…”
Section: Ba S I C S Of Sapmentioning
confidence: 99%
“…Some of these, such as haemorrhage, severe infection or evisceration are major or life‐threatening complications, requiring hospitalization. The infection rate after castration ranges from 2‐20% and in one study up to 36.7% after a standing open procedure 1–10 . Septic funiculitis occurs from the extension of a scrotal infection, and a chronically infected stump with pyogenic bacteria is defined as a “scirrhous cord.” 11 The initial surgical incision may completely heal in chronic cases of funiculitis, although the infected stump will continue to enlarge and an abscess with eventualmay produce a draining tract may develop 4,11–12 .…”
Section: Introductionmentioning
confidence: 99%